Coffee, green tea and liver cancer risk: an evaluation based on a systematic review of epidemiologic evidence among the Japanese population. (9th July 2019) - Tanaka, Keitaro; Tamakoshi, Akiko; Sugawara, Yumi; Mizoue, Tetsuya; Inoue, Manami; Sawada, Norie; Matsuo, Keitaro; Ito, Hidemi; Naito, Mariko; Nagata, Chisato; Kitamura, Yuri; Sadakane, Atsuko; et al.
Abstract : This systematic review shows that in Japanese, coffee drinking probably decreases liver cancer risk, but the evidence on an association between green tea and liver cancer is insufficient. Abstract: Background: Coffee and green tea, two popular drinks in the Japanese, have recently drawn much attention as potential protective factors against the occurrence of liver cancer. Methods: We systematically reviewed epidemiologic studies on coffee, green tea and liver cancer among Japanese populations. Original data were obtained by searching the MEDLINE (PubMed) and Ichushi databases, complemented with manual searches. The evaluation was performed in terms of the magnitude of association in each study and the strength of evidence ('convincing', 'probable', 'possible', or 'insufficient'), together with biological plausibility. Results: We identified four cohort and four case-control studies on coffee and liver cancer and six cohort and one case-control studies on green tea and liver cancer. All cohort and case-control studies on coffee reported a weak to strong inverse association, with a summary relative risk (RR) for one cup increase being 0.72 (95% confidence interval [CI] 0.66–0.79). Conversely, all studies but two cohort studies on green tea reported no association, with a corresponding summary RR of 0.99 (95% CI 0.97–1.01, P = 0.37). Conclusion: Coffee drinking 'probably' decreases the risk of primary liver cancer among the Japanese population whereas the evidence on an association between green tea and liver cancer is 'insufficient' in this population.